Sex Differences and the Role of Estradiol in Mesolimbic Reward Circuits and Vulnerability to Cocaine and Opiate Addiction - Kokane, Saurabh S.; Perrotti, Linda I. (Frontiers in Behavioral Neuroscience, 2020)
Although both men and women become addicted to drugs of abuse, women transition to addiction faster, experience greater difficulties remaining abstinent, and relapse more often than men. In both humans and rodents, these sex differences in progression to addiction are associated with hormonal cycles. Higher concentrations and fluctuating levels of ovarian hormones in females modulate the mesolimbic reward system and influence reward-directed behavior. For example, in female rodents, E2 influences dopamine activity within the mesolimbic reward system such that drug-directed behaviors that are normally rewarding and reinforcing become enhanced when circulating levels of E2 are high. Therefore, neuroendocrine interactions, in part, explain sex differences in behaviors motivated by drug reward. Here, we review sex differences in the physiology and function of the mesolimbic reward system in order to explore the notion that sex differences in response to drugs of abuse, specifically cocaine and opiates, are the result of molecular neuroadaptations that differentially develop depending upon the hormonal state of the animal. We propose that ovarian hormones, specifically estrogen/estradiol, sensitize a specific set of target neurons thereby increasing responsivity when under the influence of either cocaine or opiates or in response to exposure to drug-associated cues. These adaptations may ultimately serve to uniquely guide the motivational behaviors that underlie the factors that cause women to be more vulnerable to cocaine and opiate addiction than men.